2023
DOI: 10.1073/pnas.2310529120
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an ancient aquatic origin of the RNA viral order Articulavirales

Mary E. Petrone,
Rhys Parry,
Jonathon C. O. Mifsud
et al.

Abstract: The emergence of previously unknown disease-causing viruses in mammals is in part the result of a long-term evolutionary process. Reconstructing the deep phylogenetic histories of viruses helps identify major evolutionary transitions and contextualizes the emergence of viruses in new hosts. We used a combination of total RNA sequencing and transcriptome data mining to extend the diversity and evolutionary history of the RNA virus order Articulavirales , which includes the influenza viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This suggests that the viruses carried by ticks may have a more equal opportunity to be involved in spill-over events, potentially favouring their successful establishment in multiple animal hosts. This finding could potentially explain the phenomenon of tick-borne viruses being more inclined to act as generalists in infecting vertebrate hosts, which results in their relatively higher genetic diversity compared to other arthropods, such as mosquitoes [ 43 , 44 ]. Furthermore, we observed that regions with higher virome diversity in ticks had a greater occurrence of tick-borne pathogen (TBP) infections, underscoring the public health significance of climate-induced changes in the tick virome.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the viruses carried by ticks may have a more equal opportunity to be involved in spill-over events, potentially favouring their successful establishment in multiple animal hosts. This finding could potentially explain the phenomenon of tick-borne viruses being more inclined to act as generalists in infecting vertebrate hosts, which results in their relatively higher genetic diversity compared to other arthropods, such as mosquitoes [ 43 , 44 ]. Furthermore, we observed that regions with higher virome diversity in ticks had a greater occurrence of tick-borne pathogen (TBP) infections, underscoring the public health significance of climate-induced changes in the tick virome.…”
Section: Discussionmentioning
confidence: 99%
“…For PA, there is very low overall homology between the three full-length sequences (TiLV, Asotus1, Flavolineata), with the Zn1 binding residues being conserved but not the putative endonuclease ‘active’ site residues (Supplementary Note 9 ). Most recently, metagenomics of corals in addition to transcriptome mining has led to identification of a proposed new family, Cnidenomoviridae , within the Articulavirales order, which would now include at least four families: Orthomyxoviridae , Amnoonviridae , Quaranjaviridae , and Cnidenomoviridae 36 . Future analysis of additional sequences will undoubtedly shed more light on the evolution of Articulavirales polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that the ancient evolutionary ancestors of notable human pathogens, including influenza virus (i.e., the Orthomyxoviridae ), and SARS-CoV-2 (i.e., the Coronaviridae ) originated in aquatic species, including fish, broadly mirroring vertebrate host evolution over a period spanning more than 500 million years ( 1 , 3 , 134 , 135 ). Fish viruses typically form deep lineages on family-level viral phylogenies that depict a backbone of virus-host co-divergence over millions of years, albeit with regular occurrences of intra-class host-switching, including at the intra-class level ( 1 , 3 ).…”
Section: Diversity and Evolution Of Fish Virusesmentioning
confidence: 99%